2021
DOI: 10.1186/s12966-021-01210-y
|View full text |Cite
|
Sign up to set email alerts
|

24-hour movement behaviour profiles and their transition in children aged 5.5 and 8 years – findings from a prospective cohort study

Abstract: Background Time spent in movement behaviours, including physical activity (PA), sedentary behaviour (SB) and sleep, across the 24-h day may have distinct health consequences. We aimed to describe 24-h movement behaviour (24 h-MB) profiles in children and how profile membership changed from age 5.5 to 8 years. Methods Children in the Growing Up in Singapore Towards healthy Outcomes (GUSTO) cohort were asked to wear an accelerometer (ActiGraph-GT3X+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…Overall, high levels of MVPA were observed in the present study. Although children are normally depicted with low PA levels in large, survey-based studies ( Hallal et al, 2012 ; Aubert et al, 2018 ; Guthold et al, 2020 ), research with accelerometry has also observed MVPA levels above 60 min per day among pediatric populations ( Camiletti-Moirón et al, 2020 ; Ávila-García et al, 2021 , Llorente-Cantarero et al, 2021 ; Padmapriya et al, 2021 ), which reflect the average recommended engagement in MVPA for children and adolescents according to the most recent World Health Organization guidelines and several international PA guidelines ( Chaput et al, 2020 ; Parrish et al, 2020 ). We believe this to be a positive finding, considering the many health benefits that result from maintaining high levels of PA ( Poitras et al, 2016 ; Chaput et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, high levels of MVPA were observed in the present study. Although children are normally depicted with low PA levels in large, survey-based studies ( Hallal et al, 2012 ; Aubert et al, 2018 ; Guthold et al, 2020 ), research with accelerometry has also observed MVPA levels above 60 min per day among pediatric populations ( Camiletti-Moirón et al, 2020 ; Ávila-García et al, 2021 , Llorente-Cantarero et al, 2021 ; Padmapriya et al, 2021 ), which reflect the average recommended engagement in MVPA for children and adolescents according to the most recent World Health Organization guidelines and several international PA guidelines ( Chaput et al, 2020 ; Parrish et al, 2020 ). We believe this to be a positive finding, considering the many health benefits that result from maintaining high levels of PA ( Poitras et al, 2016 ; Chaput et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Days with ≥16 hours of activity recordings (from midnight to midnight) were considered valid, and children with at least two valid weekdays and one valid weekend day were included in the analysis. The “2015 van Hees algorithm” was applied to detect sustained inactivity and the night sleep window [ 43 45 ]. After visually inspecting the actigraphy data, we determined that sustained inactivity bouts of lasting at least 15-minutes likely represent naps; these bouts were classified as napping time.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were encouraged to wear the accelerometer 24 h per day (removing only for water-based activities: i.e., swimming/bathing) for at least 7 d, including two weekend days. Days with > 16 h/d of activity recordings (from midnight to midnight) were considered as valid [ 80 ], and the minimum amount of non-sleep data that was considered acceptable for inclusion was at least 4 days with at least 10 h of wake wear time per day, including at least one weekend day [ 81 ]. Data were collected at a sampling rate of 80 Hz downloaded in 1-s epochs with the low-frequency extension filter using the ActiLife software version 6.13 (ActiGraph LLC) and reintegrated to 15-s epochs for analysis.…”
Section: Methodsmentioning
confidence: 99%